Beispiel Nr: 04
$\sqrt[n]{a} \cdot \sqrt[n]{b} = \sqrt[n]{a\cdot b} \quad \sqrt[n]{a}:\sqrt[n]{b}=\sqrt[n]{\frac{a}{b}} \quad \sqrt[n]{\sqrt[m]{a}}=\sqrt[{mn}]{a} \\ \\ \textbf{Gegeben:} \\ {a=69 \qquad b=26 \qquad m=3 \qquad n=2}\\ \\ \textbf{Rechnung:} \\ \sqrt[2]{69} \cdot \sqrt[2]{26} = \sqrt[2]{69\cdot 26}= \sqrt[2]{1,79\cdot 10^{3}}=42,4 \\ \sqrt[2]{69}:\sqrt[2]{26}=\sqrt[2]{\frac{69}{26}} = \sqrt[2]{2\frac{17}{26}}=1,63 \\ \sqrt[2]{\sqrt[3]{69}}=\sqrt[{3\cdot 2}]{69}= \sqrt[6]{69}=2,03 \\ $